(40) Points if you answer this please Help me.
![40 Points if you answer this please Help me class=](https://us-static.z-dn.net/files/d93/4059b0c37c28937912a2a2c0083b938f.jpg)
The output values of f(8x²), f(8x²+9x) and f(-8x²) in the given function are -24x² + 4, -24x² - 27x + 4 and 24x² + 4 respectively.
Given the function in the question;
To determine the output of f(8x²), replace all the occurrence of x in the function with 8x² and simplify.
f(x) = -3x + 4
f(8x²) = -3(8x²) + 4
f(8x²) = -24x² + 4
To determine the output of f(8x²+9x), replace all the occurrence of x in the function with 8x²+9x and simplify.
f(x) = -3x + 4
f(8x²+9x) = -3(8x²+9x) + 4
f(8x²+9x) = -3(8x²+9x) + 4
f(8x²+9x) = -24x² - 27x + 4
To determine the output of f(-8x²), replace all the occurrence of x in the function with -8x² and simplify.
f(x) = -3x + 4
f(-8x²) = -3(-8x²) + 4
f(-8x²) = 24x² + 4
Therefore, the output values of f(8x²), f(8x²+9x) and f(-8x²) in the given function are -24x² + 4, -24x² - 27x + 4 and 24x² + 4 respectively.
Learn more about function composites here: https://brainly.com/question/20379727
#SPJ1